Digital Mediascapes of Transnational Korean Youth Culture - Yoon, Kyong, 1974- (Milton : Routledge, 2019)
Drawing on vivid ethnographic field studies of youth on the transnational move, across Seoul, Toronto, and Vancouver, this book examines transnational flows of Korean youth and their digital media practices. This book explores how digital media are integrated into various forms of transnational life and imagination, focusing on young Koreans and their digital media practices. By combining theoretical discussion and in depth empirical analysis, the book provides engaging narratives of transnational media fans, sojourners, and migrants. Each chapter illustrates a form of mediascape, in which transnational Korean youth culture and digital media are uniquely articulated. This perceptive research offers new insights into the transnationalization of youth cultural practices, from K-pop fandom to smartphone-driven storytelling. A transnational and ethnographic focus makes this book the first of its kind, with an interdisciplinary approach that goes beyond the scope of existing digital media studies, youth culture studies, and Asian studies. It will be essential reading for scholars and students in media studies, migration studies, popular culture studies, and Asian studies.
Description based upon print version of record.
OCLC-licensed vendor bibliographic record.
Keywords: Youth -- Korea (South); Koreans -- Canada; Mass media and youth -- Korea (South); Mass media and youth -- Canada; SOCIAL SCIENCE / Media Studies; COMPUTERS / Social Aspects / General; SOCIAL SCIENCE / Anthropology / Cultural